Manual de Funcionamiento, Mantenimiento y Aplicación Pedagógica de una Marmita en el Laboratorio de Lácteos en la Carrera de Agroindustrias de la Universidad Técnica de Cotopaxi. - Ugalde Castro, Gema Yoletty (2022)
In the present work, a manual of operation, maintenance and pedagogical application of a kettle in the Dairy Research Laboratory of the Agroindustry career of the Technical University of Cotopaxi is written. The problem of the project lies in the lack of pedagogical equipment to perform the different practices, which are required in the subjects of the curriculum of the career in Agroindustry, which directly affects students and teachers to fully carry out the practical theoretical knowledge, also there are no instructions to help preserve the life of the equipment and machines. In the present work, bibliographic research is used for the elaboration of the manuals. However, descriptive research is used to identify characteristics, requirements and parameters of the kettle; likewise, to develop a matrix according to the use given to the kettle according to the curriculum. Subsequently, the practical application was carried out according to the pedagogical applicability according to the contents of the subjects of the curriculum. The results were executed in a positive way contributing with the development of a maintenance, operation and pedagogical applicability manual of the kettle in the Dairy Research Laboratory for teachers and students of the Technical University of Cotopaxi.